Family Panorpodidae (Insecta, Mecoptera) from Baltic amber (upper Eocene): new species, redescription and palaeogeographic remarks of relict scorpionflies - Soszyńska-Maj, Agnieszka; Krzemiński, Wiesław (Zootaxa, 2013)
The history of the species-poor family Panorpodidae is very interesting due to its uneven present distribution. The only fossils of the genus Panorpodes are two species known from Baltic amber, described in 1856 and 1954. A third species, Panorpodes weitschati sp. nov., is herein described. New diagnoses and descriptions as well as new drawings of all fossil species of Panorpodes are provided, including the first illustration of the wing of P. hageni. Fossil Panorpodes display three diametrically opposed patterns of wings markings, from the highly transparent wings of P. brevicauda, through transparent wings with dark bands and spots of P. weitschati sp. nov., to the dark wings with only narrow transparent bands of P. hageni. The fossil specimens are characterized by a great variability in wing venation, even in a single specimen, similar to that of living species.